Empowering Youth through Vocational Education in Jammu and Kashmir: Assessing the Role of Tourism and Hospitality Trade in Creating Employment - Bhat, Rayees Ahmad; Ashraf, Arfat; Dar, Sameer Ahmad (MultiTech Publisher, 2024)
This study explores the potential of vocational education, particularly in the tourism and hospitality trade, to empower youth in Jammu and Kashmir by creating employment opportunities. By examining the current landscape and challenges faced by youth in the region, along with the demand for skilled workers in the tourism and hospitality sectors, this paper assesses the effectiveness of vocational education programmes in addressing unemployment and promoting sustainable livelihoods. Through quantitative analysis, the study aims to provide insights into the role of vocational education in fostering economic growth and social development in Jammu and Kashmir. Recommendations for policymakers, educators, and industry stakeholders are proposed to enhance the impact of vocational education initiatives and maximize their contribution to youth empowerment and regional prosperity.